Impact of temporary nursing staff on communication patterns: an observation study during daily nurse huddles - Julia Carolin Seelandt; Sarah Dana Schmelzer; Sina Berger; Zeynep Erden; Florian Liberatore (BMJ Open Quality)
Background Effective communication within healthcare teams is essential for efficient work coordination and patient safety. Communication in teams can take two forms: implicit and explicit, both of which play important roles in enhancing teamwork and output. However, within an unstable team constellation, maintaining effective communication can be challenging. There is limited empirical research on how temporary nursing staff impact team communication. The aim of this study is to evaluate the differences in communication patterns of permanent and temporary nursing staff.Methods In this observational study, we observed communication patterns among nurses during their daily afternoon huddles. During the live observations, we used INTERACT coding software for assessing communication patterns of permanent and temporary nursing staff. Whereby we distinguish between temporary and per diem nurses. We used lag sequential analysis to explore implicit and explicit communication patterns of temporary, per diem and permanent nursing staff. We hypothesised that temporary nursing staff primarily rely on explicit communication, whereas permanent nurses tend to rely more on implicit communication.Results Across 50 huddles with a total of 309 participating nurses, the mean huddle duration was 8.50 min and included 3074 communication transitions. We found that for per diem nurses, implicit communication was followed by explicit communication. This pattern was not observed for permanent and temporary nurses. Furthermore, for permanent and temporary nurses, preceding implicit communication was followed by implicit communication.Conclusion Our study reveals that per diem nurses, with their lower employment levels and less consistent presence, tend to shift from implicit to explicit communication. This contrasts with temporary and permanent nurses, who maintain implicit communication patterns, likely due to more developed team mental models and greater mutual trust. These findings suggest that experience and consistency in the work environment are important factors shaping communication styles among nursing staff.